Evolutionary Agroecology: Individual fitness, population yield and resource availability in wheat - Xiao-Wei Yang; Jacob Weiner; Jing-Wei Fan; Jie-Ying Ren; Wen-Yuan Luo; Feng-Min Li; Yan-Lei Du (Basic and Applied Ecology)
Evolutionary Agroecology theory predicts that the relationship between population yield and individual fitness among genotypes of a crop species is unimodal, and experimental evidence supports this. We test the theory further by investigating the role of resource availability on this relationship by comparing growth and reproductive output of three old and three modern cultivars of wheat (Triticum aestivum) in mixture and monocultures grown at three resource levels. The relationship between population grain yield and individual fitness (mean individual grain yield in mixture) of genotypes was resource dependent in a way that is consistent with the theory: when resource levels are low and limit individual growth directly, individual and population yield are positively correlated. When resource levels are high and the growth of individual plants is limited by competition for these resources, the relationship between individual fitness and population yield becomes negative. There was evidence for the unimodal relationship at the intermediate resource level. Old cultivars had higher fitness than newer cultivars at all three resource levels. Old cultivars had higher yields at low resource levels, but the newer cultivars yielded more when resource levels were high. Evaluating individual fitness and population yield in different environments may help wheat breeders to develop locally adapted, cooperative cultivars to increase production across large wheat-producing areas.